1995
DOI: 10.1002/ange.19951070310
|View full text |Cite
|
Sign up to set email alerts
|

Oligothiophene – immer länger? Synthese, Charakterisierung und rastertunnelmikroskopische Abbildung von homologen, isomerenreinen Oligo(alkylthiophenen)

Abstract: ZUSCHRIFTEN matischen Charakter zeigen. Die Aromatizitatreihe Pyrrol > Thiophen > Furan wird deutlich beschrieben, und das Cyclopentadienyl-Anion ist das ,,aromatischste" funfgliedrige Ringsystem. Eingegangen am 11. August 1994 [Z 72311 Stichworte: Ab-initio-Rechnungen . Aromatizitat . Heterocyclen [l] a) Die Literatur ist umfangreich; doch es gibt eine ausgezeichnete neue und umfassende Ubersicht: V. J. Minkin, M. N. Glukhovtsev, B. Y. Simkin, Aromaticity and Antiaromaticity, Electronic and Structural Aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 31 publications
1
23
0
3
Order By: Relevance
“…22,23,[29][30][31] For fair comparison, we also estimated the ECL with this method. Figure 2b shows the correlation between absorption energy (E max ) and inverse phenyl ring numbers (m).…”
mentioning
confidence: 99%
“…22,23,[29][30][31] For fair comparison, we also estimated the ECL with this method. Figure 2b shows the correlation between absorption energy (E max ) and inverse phenyl ring numbers (m).…”
mentioning
confidence: 99%
“…[20,21] The precursor, didodecyl-substituted quaterthiophene 5, is known to self-organize into highly regular suprastructures on surfaces [22] and in the bulk. [6a] Synthesis of the semiconductor block and the final oligothiophene-peptide hybrid 8 are shown in Scheme 1b.…”
mentioning
confidence: 99%
“…The dimerization enthalpy which was determined either by UV/VIS/NIR or EPR increases as the chain length increases. The experiments showed that radical cations of very long oligomers are almost completely dimerized at room temperature and show only weak EPR activity (see above) [169]. The correlation of the transition energies obtained for the ECnT monomeric and dimeric radical cations 283-285 also exhibit a linear dependence with the inverse chain length.…”
Section: 67-tetrahydrobenzo[b]thiophenementioning
confidence: 81%
“…As expected, the first oxidation potential for oligomers 143-146 is shifted cathodically with increasing chain length. The oxidation potentials of dodecamer 145 (Epd = 0.19 V vs Fc/Fc+) and hexadecamer 146 (Epa = 0.12V vs Fc/Fc+) are more negative than that of the structurally related poly(3-dodecyl-2,2'-bithiophene) (EFd = 0.3-0.35 V vs Fc/Fc+) [169]. This clearly indicates that longer oligomers exceed the average conjugated chain length of the parent polythiophenes which typically lie at 8-10 properly linked monomer units.…”
Section: -141mentioning
confidence: 99%